2008
DOI: 10.3390/mca13020071
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Energy Consumption Forecasting Using Genetic Programming

Abstract: Abstract-Managing electrical energy supply is a complex task. The most important part of electric utility resource planning is forecasting of the future load demand in the regional or national service area. This is usually achieved by constructing models on relative information, such as climate and previous load demand data. In this paper, a genetic programming approach is proposed to forecast long term electrical power consumption in the area covered by a utility situated in the southeast of Turkey. The empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 15 publications
0
16
0
2
Order By: Relevance
“…GA works on the survival of best fitness which combines the process of natural selection and natural genetics. GAs is found to be promising robust and suitable for load forecasting [21,22]. 4) Support Vector Machine: SVM [47,48] is a powerful technique used for data classification and regression.…”
Section: B Artificial Intelligence Based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GA works on the survival of best fitness which combines the process of natural selection and natural genetics. GAs is found to be promising robust and suitable for load forecasting [21,22]. 4) Support Vector Machine: SVM [47,48] is a powerful technique used for data classification and regression.…”
Section: B Artificial Intelligence Based Methodsmentioning
confidence: 99%
“…1) Genetic Algorithm: The genetic algorithm (GA) approach [21,22] is very effective optimization algorithm and capable to obtain global minima and maxima. Therefore best suitable for calculating minimum and maximum load leading to improved accuracy of load forecasting model.…”
Section: Soft Computing Based Forecasting Techniquesmentioning
confidence: 99%
“…Examples are genetic algorithm [54][55][56], expert system [57][58][59][60], and evolutionary computation algorithms [61].…”
Section:  Other Hybrid Methodsmentioning
confidence: 99%
“…Akay and Atak (2007) suggested a grey prediction with rolling mechanism algorithm for electricity demand forecasting. Karabulut et al (2008) showed the application of genetic programming to local load distribution forecasting in the Kahramanmaras region of Turkey. Çunkaş and Altun (2010) presented an approach based on economic indicators for Turkey's long-term electricity demand forecasting from 2008 to 2014 by using ANN.…”
mentioning
confidence: 99%